Friedrich Ratzel hatása a magyar földrajztudományban - Hajdú, Zoltán (Tér és Társadalom, 1998)
The influence of Friedrich Ratzel's (1844-1904) activity is extremely diversified and divided in time in the geography in Hungary. In Hungary the influence of Ratzel was appeared in the dispute of the geography's research object and it's place in the taxonomy of science. It also showed up in the antropogeography and political geography. The influence of Ratzel was prevailed depend on the inner evolution of the geography in Hungary and in a wider sense on the political changes in the country. It could be divided into three separable periods: Until 1948, the judgement of Ratzel and his activity was a question within the domain of science, among not only who appreciated Ratzel's activity and followed his opinion, but who queried or refused Ratzel's geographical view or it's major share. From the communistic turn in 1948 to the end of the 1980-s the judgement of Ratzel was a question of policy instead of science. In 1948 he got the fascist record and it took him unfit for good society. His activity was condemned in- stead of valuing it correctly. From 1990 the opportunities of public act of political geography are gradu- ally reforming in Hungary. The judgement of Ratzel's role in historic of ge- ography and his significance become a question within the domain of science again.